Iatrogenic Anetoderma of Prematurity: A Case Report and Review of the Literature - Laura Maffeis; Lorenza Pugni; Carlo Pietrasanta; Andrea Ronchi; Monica Fumagalli; Carlo Gelmetti; Fabio Mosca (Case Reports in Dermatological Medicine)
Anetoderma is a skin disorder characterized by focal loss of elastic tissue in the mid dermis, resulting in localized areas of macular depressions or pouchlike herniations of skin. An iatrogenic form of anetoderma has been rarely described in extremely premature infants and has been related to the placement of monitoring devices on the patient skin. Because of the increasing survival of extremely premature infants, it is easy to foresee that the prevalence of anetoderma of prematurity will increase in the next future. Although it is a benign lesion, it persists over time and can lead to significant aesthetic damage with need for surgical correction. Sometimes the diagnosis can be difficult, especially when the atrophic lesions become evident after discharge. Here, we report on a premature infant born at 24 weeks of gestation, who developed multiple anetodermic patches of skin on the trunk at the sites where electrocardiographic electrodes were previously applied. The knowledge of the disease can encourage a more careful management of the skin of extremely premature babies and aid the physicians to diagnose the disease when anetoderma patches are first encountered later in childhood.